KOMUNIKASI VERBAL DAN NON VERBAL ANTARA GURU DENGAN SISWA TUNARUNGU DI SLBN 1 PADANG PANJANG - Fitri, Ranny; Okditazeini, Vannyora (KINEMA: Jurnal Komunikasi dan Penyiaran, 2024)
This research is motivated by the fact that deaf children's ability to communicate verbally and non-verbally requires assistance from individuals who understand such communication methods. One of these sources of support is the guidance provided by school teachers on how verbal and non-verbal communication is conducted. This study involves direct observations in the classroom setting and interviews with teachers and students as the primary data sources. The type of research used by the researcher is descriptive qualitative, a study that provides an overview and analyzes data based on field observations. The phenomenological approach is employed to interpret the underlying causes of the issues being investigated. The results of this research indicate that verbal communication used by teachers at SLB N 1 Padang Panjang includes delivering clear instructions, using pictures and visualizations, employing educational aids, utilizing texts and writings, and encouraging active participation. Non-verbal communication at SLB N 1 Padang Panjang involves body language, facial expressions, hand gestures, eye contact, utilizing visual media, and employing communication aids. The appropriate use of body language will assist students in understanding the messages conveyed by the teacher.